Considering the following information:
Determine which answer is equivalent to x ( 2 x + 4 ) + 1 7 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Firstly, we have: 3 x 2 − 7 x + 5 = 3 1 1 1 1 Rearranging to = 0 gives: 3 x 2 − 7 x − 3 1 1 0 6 = 0 Using the quadratic formula to solve the equation: x = 2 a − b ± b 2 − 4 a c Inputting our values of a = 3 , b = − 7 , c = − 3 1 1 0 6 gives us: x = 2 × 3 7 ± ( − 7 ) 2 − 4 × 3 × − 3 1 1 0 6 Simplifying: x = 6 7 ± 4 9 + 3 7 3 2 7 2 Summing the square root: x = 6 7 ± 3 7 3 3 2 1 This results in two answers: x = 6 7 + 6 1 1 o r 6 7 − 6 1 1 x = 1 0 3 o r − 3 3 0 2 Now, we're told that x is a positive , non-zero integer . This means that x = 1 0 3 Now, inputting our value for x into the given equation, results in: 1 0 3 ( 2 × 1 0 3 + 4 ) + 1 7 Which simplifies to: 1 0 3 × 2 1 0 + 1 7 Which equals: 2 1 6 4 7 Now, the four options given were: 2 1 5 − 3 9 + 4 7 − 5 6 + 6 5 2 1 5 − 3 8 − 4 6 − 5 3 − 6 3 − 7 2 − 8 2 − 9 1 − 1 0 0 2 1 5 − 3 8 − 4 6 − 5 3 − 6 4 + 7 3 + 8 3 + 9 2 + 1 0 0 2 1 5 − 3 1 0 + 4 8 − 5 7 + 6 6 + 7 5 − 8 4 + 9 3 These can be inputted into a calculator, or solved on paper to give: 2 1 6 2 0 2 1 6 4 7 2 1 6 2 7 2 1 2 2 6 Therefore, the answer we are looking for is: 2 1 5 − 3 8 − 4 6 − 5 3 − 6 3 − 7 2 − 8 2 − 9 1 − 1 0 0 Which gives an answer of 2 1 6 4 7